High-Performance Liquid Chromatography Method for Simultaneous Determination of Bisphenols in Plastic Packed Dry Fruits Using Multi-walled Carbon Nanotubes as Solid Phase Extraction Sorbent - Ahmed Ali, Shazalia M.; Elamin, Manahil Babiker; Ali Omar, Mei Musa; Elbashir, Abdalla Ahmed; Aboul-Enein, Hassan Y. (Current Analytical Chemistry, 2021)
Background: Bisphenols A (BPA), bisphenol S (BPS), and bisphenol F (BPF) are manufactured chemicals found in food packaging, drink containers, lotions, toys, plastic PVC flooring, and water pipes. The aim of this work is to develop simple, rapid and reliable high-performance liquid chromatography with fluorescence detector (HPLC-FLD) method for simultaneous determination of bisphenols A (BPA), bisphenol F (BPF), and bisphenol S (BPS) in plastic packed dry fruits collected from Saudi Arabia markets. Methods: BPA, BPS and BPF in plastic packed dry fruits samples were extracted and clean up using packed Multi-Walled Carbon Nanotubes (MWCNTs) mini-column followed by analysis using HPLC-FLD. Results: The three BPs were separated within less than 12 min. The method was validated in terms of linearity, limit of detection (LOD), limit of quantification (LOQ), precision (repeatability) and accuracy (recovery). Good linearity was obtained in the concentration range of 62.25-10000 μg/L for BPS and 6.25-1000 μg/L for BPA and BPF. The LODs and LOQs were found to be 1.07, 12.09, and 0.9939 μg/L and 3.56, 40.32 and 3.13 μg/L for bisphenols BPA, BPS, and BPF, respectively. Recoveries for analytes in the samples were all within the range of 87% to 104%. Conclusion: The method was successfully applied to real dry fruit samples (i.e, dry date (Ajwa), apricot, dry grapes and figs. The results obtained revealed that all of the tested BPs were present in the samples.
Keywords: HPLC-FLD